2016
DOI: 10.1021/acssuschemeng.6b02359
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hydrophobic Properties of Cellulose Fibers via Grafting with Polymeric Epoxidized Soybean Oil

Abstract: We report on an efficient method for the formation of modified cellulose-based materials with enhanced hydrophobic properties, formed by grafting with polymeric epoxidized soybean oil (ESO) as a renewable, environmentally friendly, and low cost raw material. The grafting process occurred via ring-opening polymerization, wherein the cellulose hydroxyl groups acted as initiators in the presence of a SnCl 4 catalyst, linking the cellulose fibers and ESO via ether linkages, thereby forming a polymeric matrix. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 47 publications
0
46
0
5
Order By: Relevance
“…This indicated that the surface of ESOCA resin was hydrophilic. However, SEC biocomposites still exhibited low water absorption, as the long hydrophobic alkyl chains of ESOCA resin prevented significant amounts of water from entering [ 29 ]. There was a significant improvement in water contact angle of all SEC biocomposites, compared with that of the SESF.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the surface of ESOCA resin was hydrophilic. However, SEC biocomposites still exhibited low water absorption, as the long hydrophobic alkyl chains of ESOCA resin prevented significant amounts of water from entering [ 29 ]. There was a significant improvement in water contact angle of all SEC biocomposites, compared with that of the SESF.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to react cellulose with ESO to create a new hydrophobic material. In this reaction, the OH groups in the cellulose structure attack the epoxide rings in the presence of anhydrous stannic chloride [104] . A new polymeric adhesive with flame‐retardant properties was synthesized by Wang et al.…”
Section: Soybeanmentioning
confidence: 99%
“…Interestingly, the long chain alkane fatty acid residues in ESO can give the composites hydrophobicity, so cross-linked ESO can also work as a water-resistant film for paper that the obtained composites may be competitive in the field of packaging considering their good properties [113]. An efficient method has been reported for the formation of cellulose-based materials grafting with poly epoxidized soybean oil (PESO) with controllable hydrophobic properties [114] 1-2. A kind of PESO coated paper composites with good water-resistant property have been obtained via in situ polymerization of ESO on the surface of the paper cellulose fibers [113].…”
Section: Eso-based Polymer Compositesmentioning
confidence: 99%